Enhanced photocatalytic CO2 conversion over LaPO4 by introduction of CoCl2 as a hole mediator. Issue 41 (8th April 2016) - Pan, Bao; Zhou, Yangen; Su, Wenyue; Wang, Xuxu
Abstract : Significantly enhanced photocatalytic CO2 reduction activity over LaPO4 was achieved by introducing molecular cocatalyst CoCl2 as hole mediator. Abstract : The photocatalytic CO2 reduction over LaPO4 was significantly enhanced by simply introducing CoCl2 into the aqueous medium. The introduced CoCl2 functioned as a co-catalyst accelerating photogenerated hole transfer, by the reversible redox couple Co III –Cl/Co II –Cl, effectively suppressing the recombination of photogenerated charges.